The Application of Information Technologies in the Tourist Industry - WILK, Marlena (Journal of Advanced Research in Management; Vol 7 No 1 (2016): JARM Volume VII Issue 1(13) Summer 2016DO - 10.14505//jarm.v7.1(13).07, 2017)
The information determinates a functioning of enterprises, and especially enterprises being active in the tourist trade. A proper management of these information constitutes an important element influencing an activity of touristic enterprises. Therefore, in the article there were introduced some aspects of Information Management which is fostered by the utilization of IT systems distinctive for tourist trade sectors. There were portrayed three basic groups of economic entities participating in processes of tourist flow. The attention was also given to a variety of specific IT systems and solutions which being applied by organizations, services providers or consumers in the tourist trade contribute to supporting information management.